Towards a Better Quantification of Cyanotoxins in Fruits and Vegetables: Validation and Application of an UHPLC-MS/MS-Based Method on Belgian Products - Wannes Hugo R. Van Hassel; Julien Masquelier; Mirjana Andjelkovic; Andreja Rajkovic (Separations, 2022)
Vegetables and fruits can potentially accumulate cyanotoxins after water contaminated with cyanobacteria is used for irrigation. We developed and validated an analytical method to quantify eight microcystin congeners (MCs) and nodularin (NOD) using ultra high-performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS) in three different matrices. Strawberries, carrots and lettuce are selected as model matrices to represent the fruits/berries, leafy and root vegetables, sequentially. The validation of a UHPLC-MS/MS method in the strawberry matrix is novel. Matrix effects are observed in all three matrices. Our methodology uses matrix-matched calibration curves to compensate for the matrix effect. The implementation of our method on 103 samples, containing nine different sorts of fruits and vegetables from the Belgian market, showed no presence of MCs or NOD. However, the recoveries of our quality controls showed the effectiveness of our method, illustrating that the use of this method in future research or monitoring as well as in official food controls in fruit and vegetable matrices is valid.